“Tract(atus) 23: La théorie est attente.” Notice: “Tract(atus) 23: Theory Is Waiting.” A Note - Grelet, Gilles; Adkins, Taylor (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Gilles Grelet Title (French): “Tract(atus) 23: La théorie est attente.” Notice Title (English): “Tract(atus) 23: Theory Is Waiting.” A Note Translated by (French to English): Taylor Adkins Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 104-106 Page Count: 3 Citation (French): Gilles Grelet, “‘Tract(atus) 23: La théorie est attente.’ Notice,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 104-106. Citation (English): Gilles Grelet, “‘Tract(atus) 23: Theory Is Waiting.’ A Note,” translated from the French by Taylor Adkins, Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 104-106.